Across the Green Sea : histories from the Western Indian Ocean, 1440-1640 - Subrahmanyam, Sanjay (Connected histories of the Middle East and the Global South., 2024)
"This book connects histories from shifting viewpoints around the Western Indian Ocean showing the complexity of a dynamic oceanic system both before and after the arrival of Europeans"--